Using TENS for pain control: the state of the evidence - Vance, Carol GT (2014)
Transcutaneous electrical nerve stimulation (TENS) is a nonpharmacological intervention that activates a complex neuronal network to reduce pain by activating descending inhibitory systems in the central nervous system to reduce hyperalgesia. The evidence for TENS efficacy is conflicting and requires not only description but also critique. Population-specific systemic reviews and meta-analyses are emerging, indicating both HF and LF TENS being shown to provide analgesia, specifically when applied at a strong, nonpainful intensity. The purpose of this article is to provide a critical review of the latest basic science and clinical evidence for TENS. Additional research is necessary to determine if TENS has effects specific to mechanical stimuli and/or beyond reduction of pain and will improve activity levels, function and quality of life.